10-Fold increase (2006-11) in the rate of healthy subjects with extended-spectrum β-lactamase-producing Escherichia coli faecal carriage in a Parisian check-up centre - Nicolas-Chanoine, Marie-Hélène; Gruson, Coraline; Bialek-Davenet, Suzanne; Bertrand, Xavier; Thomas-Jean, Frédérique; Bert, Frédéric; Moyat, Mati; Meiller, Elodie; Marcon, Estelle; Danchin, Nicolas; Noussair, Latifa; Moreau, Richard; et al. (Journal of antimicrobial chemotherapy, 2013)
In 2006, 0.6% of healthy subjects living in the Paris area had extended-spectrum β-lactamase (ESBL)-producing Escherichia coli in their gut. To assess the evolution of this rate, a study identical to that of 2006 was conducted in 2011. Healthy adults who visited the IPC check-up centre in February-March 2011 and agreed to participate, provided stools and answered a questionnaire on the visit day. Stools were analysed to detect ESBL producers and to isolate the dominant E. coli population. ESBLs were molecularly characterized. For the subjects harbouring ESBL-producing E. coli, the phylogenetic group and sequence type (ST) were determined for both ESBL-producing and dominant E. coli isolates. PFGE profiles were also determined when two types of isolates had the same ST. Among the 345 subjects included, 21 (6%) had ESBL-producing E. coli faecal carriage. None of the previously published risk factors was identified. CTX-M accounted for 86% and SHV-12 for 14%. Dominant and ESBL-producing E. coli were similarly distributed into phylogenetic groups (A, 52%-48%; B1, 5%; B2, 24%-14%; and D, 19%-33%). Dominant and ESBL-producing E. coli displayed a polyclonal structure (18 STs each). However, ST10 and ST131 were identified in dominant and ESBL-producing E. coli isolates from different subjects. Most (20/21) ESBL producers were subdominant and belonged (16/21) to STs different from that of the corresponding dominant E. coli. The 10-fold increase in the rate of healthy subjects with ESBL-producing E. coli faecal carriage over a 5 year period suggests wide dissemination of these isolates in the Parisian community.